KINERJA KARYAWAN PRODUKSI CV.XYZ DIPENGARUHI OLEH DISIPLIN KERJA DAN BUDAYA ORGANISASI - Fitri Destriani; Ika Korika Swasti (JURNAL LENTERA BISNIS, 2025)
Every organization must strive to achieve company goals. One aspect that can support progress within a company is employee performance. This finding intends to see how much the contribution of work discipline and cultural organizational culture to employee performance. Distributed questionnaires in this study were distributed to 40 production employees who were used as samples. The data was then processed using Smart Partial Least Square (PLS) to determine the validity, reliability, and hypothesis tests. This study shows the results that employee performance is positively influenced by work discipline and organizational culture. Employees who are able to obey all company regulations and are able to apply the culture set by the company will make employees able to improve their performance.